2022
DOI: 10.1007/s00784-022-04531-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of periodontal indices among non-smokers, tobacco, and e-cigarette smokers: a systematic review and network meta-analysis

Abstract: Objectives The detrimental effect of tobacco smoking on periodontal health is well known, while the effect of electronic cigarette on periodontal parameters has been less investigated. The aim of the present systematic review was to compare periodontal indices in three categories of patients: traditional cigarette smokers (TS), e-cigarette smokers (ES), and non-smokers (NS). Materials and methods An electronic search was conducted for studies published unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
1
17
0
2
Order By: Relevance
“…Six systematic reviews, all moderate quality, examined the impact of conventional tobacco smoking and/or e‐cigarette use on a range of oral health outcomes 8,32–36 …”
Section: Resultsmentioning
confidence: 99%
“…Six systematic reviews, all moderate quality, examined the impact of conventional tobacco smoking and/or e‐cigarette use on a range of oral health outcomes 8,32–36 …”
Section: Resultsmentioning
confidence: 99%
“…Our results suggested that smoking and reasons of extraction had no relation to the Healing Index; however, it must be pointed out that the number smoked cigarettes and the type of smoking (traditional vs. electronic) was not registered, and this could have influenced the results [ 71 ]. Dealing with the reason of extraction, it must be underlined that all patients assumed an antibiotic therapy that could have influenced the results.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine generates contraction of vascular endothelial cells, making gingivitis less clinically evident furthermore it reduces crevicular fluid and immune cells. Untreated, gingivitis easily passes into the periodontitis stage [17].…”
Section: Pathogens Found In Smokersmentioning
confidence: 99%